Integrating Environmental Health into Disaster-Resilient Villages: Strategies, Challenges, and Solutions in Surakarta, Indonesia - Subarno, Anton; Koesuma , Sorja; Sukatiman (Universitas Airlangga, 2025)
Introduction: Surakarta is a city plagued by challenges related to critical disaster vulnerability, with 26 out of its 54 urban villages lacking disaster-resilient status despite facing frequent floods, landslides, and dense settlement fires that threaten environmental and public health. Therefore, the present study examined the implementation of disaster-resilient village programs in the city, focusing on environmental health integration and local capacity development. Methods: This qualitative study employed a case study analysis of four villages in Surakarta. The data collection involved in-depth interviews with government officials, community leaders, and residents, complemented by participatory observation and document analysis. The analysis utilized the qualitative comparative analysis framework, incorporating source and method triangulation. Results and Discussion: This study identified key environmental health integration strategies through water quality monitoring, air quality assessment, and sanitation infrastructure development. It was found that improved water quality monitoring reduced waterborne diseases by 45% after flood, enhanced air quality surveillance decreased respiratory problems by 38% in dense settlements, and upgraded sanitation infrastructure lowered disease transmission rates by 52% in landslide-prone areas. Conclusion: The successful implementation of disaster-resilient villages depends on the villages’ level of environmental health integration, as evidenced by reduced post-disaster disease rates, effective hazard mitigation, and decreased health impacts in the observed villages. These findings emphasize the urgent need for environmental health-focused disaster resilience programs in vulnerable urban villages.